Labour law effects of death and loss of legal capacity of an employer acting in the capacity of a natural person - Dragićević Marija (Zbornik Radova Pravnog Fakulteta u Nišu, 2023)
The employer may act in the legal capacity of a natural person or a legal entity. In the former case, the subject of an employment relationship is a natural person per se or a natural person in the capacity of a sole trader or a freelancer. In the latter case, given that a natural person is identified with his/her own enterprise (as they constitute one body), the question arises what happens in the event of a change in the legal status of a natural person as the employer (a holder of a sole proprietorship), which will primarily take place in the event of death or loss of legal capacity. Considering that the labour legislation of the Republic of Serbia does not provide an answer to this question, the author will address this question by seeking answers within the framework of general rules of labour, inheritance, family and company legislation. In that sense, the paper analyzes the effects of death and loss of legal capacity of an employer (a natural person) on the existing employment relations. The author aims to respond to the question whether the employer's death necessarily causes the termination of employment, or whether such employment may be continued by the employer's successors (in which case, it may be considered as the change of employer). In particular, the author focuses on the provisions of the Business Companies Act, which regulate the possibilities to continue conducting the business in the event of the sole trader's death while implicating their shortcomings, unclarities and issues they cause in the interpretation and practical application thereof. In that context, the author examines the legal grounds enabling the successor to take over the sole trader business, the subject matter of such succession, the labour law status of employees, and the possibility for the co-successors' community (a number of natural persons) to act in the capacity of the employer.